ESTABISHING OBJECTIVES FOR PUBLISHED CORPORATE ACCOUNTING REPORTS. - Rappaport, Alfred (The Accounting Review, 1964)
Abstract In response to the increasing significance of corporate information in the present economy, accountants have demonstrated an active interest in developing a cohesive and useful framework to guide the selection, measurement, and communication of information for published corporate accounting reports. Despite some notable contributions, especially over the past three decades, most qualified observers would undoubtedly agree that such a framework or theory has not been satisfactorily developed. The emerging philosophy of accounting research characterized by a commitment to a scientific attitude has enhanced greatly the potential for accounting theory. The essential purposes of this paper is to demonstrate that objectives for published corporate accounting reports should be an integral part of the development of corporate accounting theory formation. It also proposes a methodology for the development of objectives for published corporate accounting reports. The paper also tries to employ the proposed methodology in the logical development of basic objectives for published corporate accounting reports.